2016
DOI: 10.1155/2016/5206268
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Extraction of Appendix from Ultrasonography with Self-Organizing Map and Shape-Brightness Pattern Learning

Abstract: Accurate diagnosis of acute appendicitis is a difficult problem in practice especially when the patient is too young or women in pregnancy. In this paper, we propose a fully automatic appendix extractor from ultrasonography by applying a series of image processing algorithms and an unsupervised neural learning algorithm, self-organizing map. From the suggestions of clinical practitioners, we define four shape patterns of appendix and self-organizing map learns those patterns in pixel clustering phase. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…As stated in section 1, our previous approach using SOM [26] works nicely in most cases but we found that SOM based pixel clustering was subtle when there was a loss of intensity information during its repetitive learning process to select the single winning neuron. In failed extraction cases, it could not locate the inflamed appendix since the lost intensity information misguided the software to remove the appendix object as noise.…”
Section: Semi-dynamic Control Of Fcm In Appen-dix Extractionmentioning
confidence: 79%
See 3 more Smart Citations
“…As stated in section 1, our previous approach using SOM [26] works nicely in most cases but we found that SOM based pixel clustering was subtle when there was a loss of intensity information during its repetitive learning process to select the single winning neuron. In failed extraction cases, it could not locate the inflamed appendix since the lost intensity information misguided the software to remove the appendix object as noise.…”
Section: Semi-dynamic Control Of Fcm In Appen-dix Extractionmentioning
confidence: 79%
“…Intelligent pixel clustering methods [6,12,25,26] are designed to enhance the brightness contrast and form an appendix object from US. A method uses fascia as a predictor of the appendix location and uses fuzzy binarization techniques to determine the appendix boundaries with various image processing algorithms [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, pixel clustering approaches have been successfully applied to detect the target organ from ultrasonography or X-ray images. Some examples of such approaches include detecting brain tumor [13,14], brachial artery [15], cervical vertebrae [16], lung cancer [17], inflamed appendix [18], ganglion cyst [19] and breast image segmentation [20]. Thus, in this paper, we take K-means based pixel clustering approach [16,21] to this automatic segmentation problem.…”
Section: Introductionmentioning
confidence: 99%